Predictive factors for recurrence after lower limb deformity correction in hypophosphatemic rickets - Suparatchatadej C. (2023)
Background: Surgical treatment for severe lower limb deformities in patients with hypophosphatemic rickets has shown satisfactory outcomes. However, the rates of recurrence of deformities after surgical correction were high, and studies on predictive factors of recurrence were limited. This study aimed to determine the predictive factors for the recurrence of lower limb deformities after surgical correction in patients with hypophosphatemic rickets, and the effects of each predictor on the recurrence of deformities. Methods: We retrospectively reviewed the medical records of 16 patients with hypophosphatemic rickets aged 5–20 years and who had undergone corrective osteotomies between January 2005 and March 2019. Demographic data from the patients, biochemical profiles, and radiographic parameters were collected. Univariable Cox proportional hazard analyses of recurrence were performed. Kaplan–Meier failure estimation curves for deformity recurrences of potential predictors were created. Results: A total of 38 bone segments were divided into 2 groups: 8 segments with recurrent deformities and 30 segments without recurrent. The average follow-up time was 5.5 ± 4.6 years. Univariable Cox proportional hazard analyses of recurrence found that an age < 10 years (hazard ratio [HR], 5.5; 95% CI, 1.1–27.1; p = 0.04), and gradual correction by hemiepiphysiodesis (HR, 7.0; 95% CI, 1.2–42.7; p = 0.03) were associated with recurrence after surgery. The Kaplan–Meier failure estimation for deformity recurrences by age at the time of surgery also achieved a statistically significant difference between ages < 10 years and those > 10 years (p = 0.02). Conclusions: Identifying predictive factors for the recurrence of lower limb deformities after surgical correction in hypophosphatemic rickets can assist in early recognition, proper intervention, and prevention. We found that an age < 10 years at the time of surgery was associated with recurrence after deformity correction and gradual correction with hemiepiphysiodesis may also be a potential factor affecting the recurrence.